THE EFFECT OF USING THE PEER-ASSISTED LEARNING STRATEGY TOWARD STUDENTS’ READING COMPREHENSION AT SMPN 2 2 X 11 KAYUTANAM - Oliviana, Leona; Hayati, Amal (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2017)
The purpose of this research was to find the effect of using Peer-Assisted Learning Strategy (PALS) toward students’ reading comprehension at SMPN 2 2 X 11 Kayutanam. This experimental research focussed on post-test only control design. The population of this research was all of students grade VIII of SMPN 2 2 X 11 Kayutanam. There were two classes as the sample; VIII.5 as the experimental class which consisted of 20 students and class VIII.4 as the control class which consisted of 21 students. The sample was chosen by using cluster sampling technique. After conducting the treatments, the result showed that Peer-Assisted Learning Strategy (PALS) give positive effect towards students’ reading comprehension as proved by statistically calculation. The calculation showed that the mean score of the experiment class was 63.6 with standard deviation 10.61. On the other hand, the mean score of control class was 59.24 with standard deviation 12.3. The result of t-test with degree of freedom 39 and α 0.05 found that tcalculate 8.55 < ttable 1.685.